Popular Culture as a Creation of Art in Frank O'Hara Selected Poems - Hisham Abdulsattar Waheed, MA Student; Anan Alkass Yousif, PHD (مجلة الآداب, 2022)
While the significance of Abstract Expressionism in Frank O’Hara’s poetry has been widely discussed in academic researches, this paper aims at exploring the role of popular culture in his poetry and the significance of Pop Art in shaping his poetic production. The paper argues that O’Hara’s employment of topics, consumer and mundane objects, and images taken from popular culture and mass media was the very means to create an unorthodox art. Such an art challenged and opposed the American elitism of high culture and good taste, the very standards by which the artistic value of a piece of art was measured.